2009
DOI: 10.1074/jbc.m806144200
|View full text |Cite
|
Sign up to set email alerts
|

Trihydrophobin 1 Interacts with PAK1 and Regulates ERK/MAPK Activation and Cell Migration

Abstract: The Rac1/Cdc42 effector, p21-activated kinase (PAK), is activated by various signaling cascades, including receptor-tyrosine kinases and integrins, and regulates a number of processes such as cell proliferation and motility. PAK activity has been shown to be required for maximal activation of the canonical RAF-MEK-MAPK signaling cascade, possibly because of PAK co-activation of RAF and MEK. Here we have shown that trihydrophobin 1 (TH1), originally identified as a negative regulator of A-RAF kinase, also inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 63 publications
1
48
0
Order By: Relevance
“…We then conducted western blot analysis to measure the protein levels of integrin a V and b 3 subunits, and the focal adhesion kinase (FAK) and its phosphorylation status, a critical mediator of integrin signaling (Mitra and Schlaepfer, 2006; van Nimwegen and van de Water, 2007). We also detected the expression of p21-activated kinase (PAK)-1 and its phosphorylation status, a downstream molecule of integrin a V b 3 signaling pathway (Zhou and Kramer, 2005;Cheng et al, 2009). Our results showed that the knockdown of JWA upregulated FAK and PAK-1 expression and activated their phosphorylation status in both B16 cells (Figure 3b, left panel) and A375 cells (Figure 3b, right panel).…”
Section: Jwa Suppresses Cell Invasion and Matrix Metalloproteinases (mentioning
confidence: 84%
See 1 more Smart Citation
“…We then conducted western blot analysis to measure the protein levels of integrin a V and b 3 subunits, and the focal adhesion kinase (FAK) and its phosphorylation status, a critical mediator of integrin signaling (Mitra and Schlaepfer, 2006; van Nimwegen and van de Water, 2007). We also detected the expression of p21-activated kinase (PAK)-1 and its phosphorylation status, a downstream molecule of integrin a V b 3 signaling pathway (Zhou and Kramer, 2005;Cheng et al, 2009). Our results showed that the knockdown of JWA upregulated FAK and PAK-1 expression and activated their phosphorylation status in both B16 cells (Figure 3b, left panel) and A375 cells (Figure 3b, right panel).…”
Section: Jwa Suppresses Cell Invasion and Matrix Metalloproteinases (mentioning
confidence: 84%
“…The phosphorylation of FAK on Tyr397 site results in the activation of Rac. Rac then leads to the activation of PAK, which enhances actin polymerization (Zhou and Kramer, 2005;Cheng et al, 2009). Analysis of the integrin a V b 3 promoter revealed many Sp1 binding sites that are important for integrin a V b 3 transcription in B16 and A375 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The total and phosphorylated levels of ERK, MEK, p38 and JNK proteins were quantified using appropriate sandwich ELISA kits (Cell Signaling Technology, MA, USA). MEK-cRaf complex levels and free (unbound) MEK levels were quantified according to previously described protocols with modifications (see the electronic supplementary material, figure S1) [46][47][48]. The total MEK levels are presented in optical densities and phosphorylated MEK, MEK-cRaf and pMEK-cRaf levels are normalized to total MEK levels.…”
Section: Erk Jnk P38 Mapk Pathways Activationmentioning
confidence: 99%
“…As a cyclin-dependent kinase, CDK11 p58 interacts with cyclin D3 to regulate G 2 /M phase cell cycle progression (14) and represses AR-mediated transactivation through phosphorylating AR to inhibit androgen-dependent proliferation of prostate cancer cells (15). CDK11 p58 is also involved in the negative regulation of estrogen receptor and vitamin D3 receptor, the other two nuclear transcription factors (16,17).…”
Section: Activity (12) Previous Researches Have Indicated That Cdk11mentioning
confidence: 99%